(3bUjOI aj eOM GdfHj Udi Gddg Ydjg hSdes - (3GdMehj, GHf MLI, Ydj Hf YHO Gddg Hf MLI, J(B837(3g`s
(3ChdgG (B:s
(3TOJ Hce GdYTGb deG JQfehG (B*** (3aYfhG hbO WGH GdebGe hReR ehGs
(3BNQgG (B:s
(3Ydjc SdGe fTQg cdeG HOG (B*** (3Hg jJZGdi GdWjH GdeSc jNJes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 67s
(3eYLe GdeDdajf(B: 2 / 465s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs